Grade-cost relationships within Australian underground gold mines – A 2014–2017 empirical study and potential value implications. (June 2019) - Ulrich, Sam; Trench, Allan; Hagemann, Steffen
Abstract: Quantitative analysis of publicly reported quarterly cost data from 23 Australian underground gold mines in the period 2014–2017 identifies consistent, statistically significant, relationships between gold grade and costs at the individual mines. Higher gold grades are associated with lower production costs throughout the dataset. The resultant regression lines for individual mines in their simplest mathematical form are a power function ( f(x) = ax b ), where a is the scaling factor and b the rate of growth or decay in the grade-cost relationship. The general formula for the relationship between average feed grade and All-in Sustaining Costs (AISC) on a mine-by-mine basis is: AISC=exp(scaling coefficient) × Average Feed Grade (AISC decay rate) The specific grade-cost regressions are, however, markedly different between mines. For the typical grade-range of underground gold mines, costs at some mines, 'Type 1', display greater sensitivity to feed grade (AISC decay rate ≤ −1.0). At other mines the grade-cost relationship, although still indicating that higher grades are linked with lower costs, reveals lesser cost sensitivity to feed grade. We term these mines either 'Type 2' (AISC decay rate −0.6 to −1.0), or 'Type 3' (AISC decay rate > −0.6) where changes in feed grades correspond with lesser sensitivity to changes in costs. Although the underlying causes of the different grade-cost relationships remain uncertain, the contrasting relationships are clear and statistically significant. The identification of these contrasting grade-cost functions has major implications for the gold industry. For example, the data imply that asset-level mine transactions in the gold industry have inherently different risk characteristics depending upon whether the transacted asset is a Type 1, Type 2 or Type 3 gold mine in grade-cost terms. Disparities between recently mined grades and remaining Ore Reserve grades represent one dimension of the risk implications and the potential increase or decrease in mine value. At a steady gold price, the future cost performance of a gold mine will differ markedly based on the Ore Reserve grade to recently mined grade difference and the Types 1, 2 or 3 mine-type. Highlights: Statistically significant relationships between gold grade and costs observed. Three grade-cost categories proposed based on a mine's cost sensitivity to grade. Implications of grade-cost relationships for mine owners and those purchasing mines. Current Ore Reserve gold grades indicate higher future costs for the majority of mines.